Permeability Enhancement of Methotrexate Transdermal Gel using Eucalyptus oil, Peppermint Oil and Olive Oil(Conference Paper )# - Ali Ashoor , Jamal; M. Mohsin, Jinan; Mohsin, Hussein Mohammed; W. Mahde, Basam; M. Gareeb, Mowafaq (Iraqi Journal of Pharmaceutical Sciences, 2022)
Abstract Objective: the idea of this study to improve transdermal permeability of Methotrexate using eucalyptus oil, olive oil and peppermint oil as enhancers.Method: eucalyptus oil (2% and 4%), peppermint oil (2% and 4%) and olive oil (2% and 4%) all used as natural enhancers to develop transdermal permeability of Methotrexate via gel formulation. The gel was subjected to many physiochemical properties tests. In-vitro release and permeability studies for the drug were done by Franz cell diffusion across synthetic membrane, kinetic model was studied via korsmeyer- peppas equation.Result: the results demonstrate that safe, nonirritant or cause necrosis to rats’ skin and stable till 60 days gel was successfully formulated.Methotrexate penetration alone without enhancer is only about 20%, while using enhancers reach to 85%, 99% and 90% with eucalyptus oil 4%, peppermint oil 4% and olive oil 4% respectively after 24 hours.Conclusion: Methotrexate transdermal gel was prepared and evaluated fruitfully in-vitro with a good permeation across semipermeable membrane. The results indicated that using of peppermint oil as enhancer have superiority to enhance the transdermal permeation of the Methotrexate.